Implementation of Sharia Fund Collection and Financing Products at BMT NU in Kraksan City - Abdul Aziz Irfan; Ahmad Zainal Abidin (IJED: International Journal of Economy Development Research, 2025)
This study aims to examine the mechanisms of Islamic fund mobilization implemented by BMT NU Kota Kraksaan through savings and member deposit products based on wadiah and mudharabah contracts, to understand the process of Islamic financing distribution along with the contracts applied, and to analyze the conformity of BMT’s operational practices with Islamic banking theory. This research employs a qualitative approach using a case study method. The research location is BMT NU Kota Kraksaan, Probolinggo Regency. Research informants include the BMT manager, staff/employees, and members or customers directly involved in Islamic fund mobilization and financing products. Data were collected through observation, interviews, and documentation, while data analysis was conducted using descriptive qualitative methods. The findings indicate that BMT NU Kota Kraksaan has consistently implemented Islamic fund mobilization products based on wadiah and mudharabah contracts in accordance with Sharia principles. On the financing side, BMT distributes funds through murabahah, mudharabah, musyarakah, ijarah, and qardh contracts, which are predominantly utilized as capital for members’ micro-enterprises. BMT’s operational practices also demonstrate the application of transparency, fairness, and partnership principles between the institution and its members. Nevertheless, several challenges remain, particularly the limited understanding of some members regarding Sharia contracts and constraints related to the administrative system.